A New Methodology of Design and Development of Serious Games - André F. S. Barbosa; Pedro N. M. Pereira; João A. F. F. Dias; Frutuoso G. M. Silva (International Journal of Computer Games Technology)
The development of a serious game requires perfect knowledge of the learning domain to obtain the desired results. But it is also true that this may not be enough to develop a successful serious game. First of all, the player has to feel that he is playing a game where the learning is only a consequence of the playing actions. Otherwise, the game is viewed as boring and not as a fun activity and engaging. For example, the player can catch some items in the scenario and then separate them according to its type (i.e., recycle them). Thus, the main action for player is catching the items in the scenario where the recycle action is a second action, which is viewed as a consequence of the first action. Sometimes, the game design relies on a detailed approach based on the ideas of the developers because some educational content are difficult to integrate in the games, while maintaining the fun factor in the first place. In this paper we propose a new methodology of design and development of serious games that facilitates the integration of educational contents in the games. Furthermore, we present a serious game, called “Clean World”, created using this new methodology.